Monitoring change of urine specific gravity levels of the wrestlers in an official wrestling tournament - Guder, Ferhat (Progress in Nutrition, 2020)
Study Objectives: Wrestling is a weight sport with a weight classification and wrestlers is performed weight loss frequently before the wrestling competitions and they exposed dehydration. In this context, the aim of this study was to monitor the change in the urine specific gravity (USG) of wrestlers in an official wrestling tournament. Thirty-six wrestlers competing in an official wrestling tournament were included in the study. Methods: Bioelectric impedance analyzer and refractometer were used to determine the change of body weights and the USG levels of the wrestlers between the weigh-in and the competition times. Shapiro-Wilk test was used for the normality test of the obtained data. Wilcoxon Signed-Rank test was used to analyze non-normally distributed data. Results: According to the results of this study, it was determined that there was no difference in the body weights of the wrestlers between the weigh-in and the competition times, whereas there was a difference in the USG levels. Accordingly, although USG levels decreased, it could not be reduced to the reference range between the weigh-in and the competition times. Conclusion: These results indicate that the lose body weight before the competition is regained between the weigh-in and the competition times, whereas dehydration in the USG levels continues in the wrestlers.